A fine-tuned azobenzene for enhanced photopharmacology in vivo. Issue 11 (18th November 2021) - Gutzeit, Vanessa A.; Acosta-Ruiz, Amanda; Munguba, Hermany; Häfner, Stephanie; Landra-Willm, Arnaud; Mathes, Bettina; Mony, Jürgen; Yarotski, Dzianis; Börjesson, Karl; Liston, Conor; Sandoz, Guillaume; Levitz, Joshua; et al.
Summary: Despite the power of photopharmacology for interrogating signaling proteins, many photopharmacological systems are limited by their efficiency, speed, or spectral properties. Here, we screen a library of azobenzene photoswitches and identify a urea-substituted "azobenzene-400" core that offers bistable switching between cis and trans with improved kinetics, light sensitivity, and a red-shift. We then focus on the metabotropic glutamate receptors (mGluRs), neuromodulatory receptors that are major pharmacological targets. Synthesis of "BGAG12, 400, " a photoswitchable orthogonal, remotely tethered ligand (PORTL), enables highly efficient, rapid optical agonism following conjugation to SNAP-tagged mGluR2 and permits robust optical control of mGluR1 and mGluR5 signaling. We then produce fluorophore-conjugated branched PORTLs to enable dual imaging and manipulation of mGluRs and highlight their power in ex vivo slice and in vivo behavioral experiments in the mouse prefrontal cortex. Finally, we demonstrate the generalizability of our strategy by developing an improved soluble, photoswitchable pore blocker for potassium channels. Graphical abstract: Highlights: Azobenzene tuning for red-shift and enhanced sensitivity, efficiency and speed Improved photoswitches enable ultra-efficient control of GPCRs and ion channels Acute modulation of working memory via mGluR2 photo-activation in the mouse mPFC Abstract : Gutzeit et al . report a chemical screen that reveals an urea-conjugated azobenzene with optimal photoswitching properties. This enables the development and characterization of optimized tethered and freely diffusible photoswitchable ligands for GPCRs and ion channels, including the rapid manipulation of working memory via mGluR2 photo-activation in vivo in freely moving mice.